Taking care of our earth for better future through green geological engineering practices - Pyi Soe Thein, Pyi Soe Thein (2013)
Sulawesi Island, eastern Indonesia, is located at the junction between the converging Pacific, Indo-Australian and the Eurasian Plates. One of the major structures in Central Sulawesi is the Palu-Koro Fault System, which extends NNW-SSE direction and cross cuts Sulawesi along more than 300km, from the North Sulawesi trench pass Palu Bay, southward turn to the SE connect to the Matano and Lawanopo Faults, and further eastward, both faults join to Tolo trench.